2011
DOI: 10.1007/s00436-011-2361-0
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomus (Transphlebotomus) mascittii Grassi, 1908, in Carinthia: first record of the occurrence of sandflies in Austria (Diptera: Psychodidae: Phlebotominae)

Abstract: During an entomology survey in July 2009 and July 2010, 4 males and 22 females of Phlebotomus (Transphlebotomus) mascittii were caught in southeastern Carinthia. These are the first documented records of the occurrence of Phlebotominae in Austria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 15 publications
1
22
0
3
Order By: Relevance
“…perniciosus, which accounted for only 0.48 % of captures in the study area, is fairly abundant in the Provence region [26]. In agreement with previous data [27], Ph. mascittii represented a very small proportion of the total sandfly captures (0.11 %).…”
Section: Discussionsupporting
confidence: 89%
“…perniciosus, which accounted for only 0.48 % of captures in the study area, is fairly abundant in the Provence region [26]. In agreement with previous data [27], Ph. mascittii represented a very small proportion of the total sandfly captures (0.11 %).…”
Section: Discussionsupporting
confidence: 89%
“…Until the first and hitherto unique finding of sandflies in Austria near the Carinthian/Slovenian border in the year 2009 (Naucke et al 2011), Austria was believed to be free of sandflies. However, it had already been shown that only a moderate increase in temperature would lead to conditions favourable for the occurrence of sandflies in large parts of the country (Aspöck et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent years, the autochthonous occurrence of sandflies in Central Europe was confirmed by further catches in Germany and Belgium. Recently, the occurrence of Phlebotomus ( Transphlebotomus ) mascittii was also documented in Austria, in Carinthia close to the border to Slovenia (Naucke et al 2011). These recent sandfly catches together with autochthonous cases of leishmaniasis and Phlebovirus infections in Central Europe, particularly in Germany (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In Austria, P. mascittii was first recorded in 2009 [12]. Since then, several field studies in various regions of Austria have been conducted [16, 18], and interestingly, P. mascittii was only found close to human dwellings, usually farms with livestock and companion animals, corroborating its adaption to man-made environments.…”
Section: Introductionmentioning
confidence: 99%